2004
DOI: 10.1152/ajpcell.00175.2004
|View full text |Cite
|
Sign up to set email alerts
|

cAMP-activated maxi-Cl channels in native bovine pigmented ciliary epithelial cells

Abstract: The eye's aqueous humor is secreted by a bilayered ciliary epithelium comprising pigmented (PE) and nonpigmented (NPE) epithelial cell layers. Stromal Cl(-) enters the PE cells and crosses gap junctions to the NPE cells for release into the aqueous humor. Maxi-Cl(-) channels are expressed in PE cells, but their physiological significance is unclear. To address this question, excised patches and whole native bovine PE cells were patch clamped, and volume was monitored by calcein fluorescence. In symmetrical 130… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 39 publications
2
38
0
Order By: Relevance
“…These channels were similar to those observed in cultured cortical astrocytes from rats [4,49,50] and mice [5][6][7]51] as well as in a rat astrocytic RGCN cell line [52]. In epithelia, the urinary bladder [53], gastric [54], pancreatic [55][56][57], colonic [58][59][60], airway [61][62][63], choroid plexus [64], bile duct [65,66], ciliary [67][68][69], renal [9,19,[70][71][72][73][74][75][76][77][78], vestibular [79], placental [80][81][82][83][84][85][86], ruminal [87] and ovarian [84] epithelial cells were also found to express the maxianion channel with properties similar to those of excitable cells. Resembling maxi-anion channels were also found in fibroblasts [14,…”
Section: Expression Pattern Of the Maxi-anion Channelsupporting
confidence: 83%
See 1 more Smart Citation
“…These channels were similar to those observed in cultured cortical astrocytes from rats [4,49,50] and mice [5][6][7]51] as well as in a rat astrocytic RGCN cell line [52]. In epithelia, the urinary bladder [53], gastric [54], pancreatic [55][56][57], colonic [58][59][60], airway [61][62][63], choroid plexus [64], bile duct [65,66], ciliary [67][68][69], renal [9,19,[70][71][72][73][74][75][76][77][78], vestibular [79], placental [80][81][82][83][84][85][86], ruminal [87] and ovarian [84] epithelial cells were also found to express the maxianion channel with properties similar to those of excitable cells. Resembling maxi-anion channels were also found in fibroblasts [14,…”
Section: Expression Pattern Of the Maxi-anion Channelsupporting
confidence: 83%
“…The channel is thought to participate in the Cl -efflux during cell volume regulation in cortical collecting duct epithelium [9,75], pigmented ciliary epithelial cells [68], lymphocytes [102,104], myoblasts [23], placenta [80], neuronal cells [3] and astrocytes [4]. The maxi-anion channel is expressed in the ciliary epithelium, where it may participate in the aqueous humor secretion [67,130], and in the hepatic bile duct, where it could be involved in bile formation [65,66]. Efflux of Cl -ions during apoptotic cell shrinkage is also thought to occur via maxi-anion channels in neuronal cells [46].…”
Section: Transportmentioning
confidence: 99%
“…In contrast to its direct activation of maxi-Cl Ϫ channels of PE cells (24,27), cAMP can lower gap junctional communication indirectly by activating PKA, at least under our experimental conditions. This observation adds to the literature documenting that cAMP exerts actions expected both to stimulate and inhibit net aqueous humor formation (10,21).…”
Section: Discussionmentioning
confidence: 59%
“…The previously described procedure for cell isolation and preparation (24) was slightly modified to increase the yield of PE-NPE cell couplets. Briefly, fresh bovine eyes were obtained from a local abattoir.…”
Section: Methodsmentioning
confidence: 99%
“…Also experiments performed using patch clamp techniques have demonstrated that cAMP can activate chloride channels such as the maxi-Cl 2 , although its physiologic role in situ has not been fully elucidated (Mitchell and Civan, 1997;Do et al, 2004b). Small changes in cAMP cytosolic concentrations may produce vast changes in the chloride efflux.…”
Section: Discussionmentioning
confidence: 99%